PERTUMBUHAN BIBIT KELAPA SAWIT PADA PEMBERIAN KOMPOS JANJANG KOSONG KELAPA SAWIT DI PRE NURSERY PADA TANAH BEKAS TAMBANG BATUBARA - Frans Suheru Ginting; Nyimas Myrna Elsa Fathia (Bioplantae, 2015)
This research aims to know the growth of oil palm seeds and composition of empty oil palm bunches of compost and ex- coal mining soil as a medium for planting oil palm seedlings in pre nursery. This research consists of 4 level of treatment, namely k0: top soil as a control, k: the composition of media from ex-coal mining soil andempty oil palm bunches compost (75%: 25%), k1: the composition of media from excoalminingsoilandempty palm bunches of compost (50%: 50%), k2: the compositionof media from ex-coal mining soil and empty oil palm bunches of compost (25%: 75%).Each treatment was repeated 6 times, so there are 24 units of treatment. The variablesmeasured in this study are number of leaves, stem diameter, total dry weight, leaf areaand dry weight of roots. The results showed that the composition of media from ex-coalmining soil and empty palm bunches of compost can increase oil palm growth seedling.The treatment of 75 % of media from ex coal mining soil: 25% empty of oil palmbunches of compost show the highly number of leaves, stem diameter, total dry weight,leaf area, and dry weight of roots.